The Nottwil Standard-Development and Implementation of an International Classification of Functioning, Disability and Health-Based Clinical Standard Assessment for Post-acute Rehabilitation After Newly Acquired Spinal Cord Injury - Scheel-Sailer, Anke; Lampart, Patricia; Selb, Melissa; Baumberger, Michael; Gmünder, Hans Peter; Sigrist-Nix, Diana; Schmitt, Klaus; Stucki, Gerold (Frontiers in Rehabilitation Sciences, 2021)
Introduction: Assessments during rehabilitation of spinal cord injury (SCI) align with the World Health Organization's classifications and national quality requirements. This paper aims to report on the development and first implementation experiences of an institutional standard of assessments performed after newly acquired SCI. Setting: Specialized SCI acute care and post-acute rehabilitation clinic in Switzerland. Methods: A situation analysis of an interdisciplinary post-acute SCI rehabilitation program was performed. The results informed a subsequent consensus-based selection of assessments, and an information and implementation strategy. Linking to the ICF Core Set for SCI in post-acute settings and ICF Generic-30 Set was performed. The Nottwil Standard was piloted for 18 months. Results: Situation analysis: A battery of 41 assessments were irregularly performed during initial rehabilitation after newly aquired SCI. Selection of assessments: A multidisciplinary group of clinicians agreed on 10 examinations, 23 assessments and two questionnaires that make up the Nottwil Standard. In total, 55 ICF categories are covered, including most of the ICF Generic-30 Set categories. The implementation strategy included Executive Board commitment, a structured improvement project, guidelines for documentation and assessments, a manual controlling system, and staff training on the Nottwil Standard. Pilot phase: 54 persons with paraplegia and 42 with tetraplegia (75 male; 21 female) were included. Twenty-seven assessments out of 33 assessments were performed in more than 80% of all observed patients' rehabilitation. Conclusion: Implementation of a standard assessment schedule was feasible but required a well-structured process with good communication strategy and controlling mechanism, and full engagement of involved professions.